Physiological and physicochemical behavior of guamara (Bromelia pinguin) and cocuixtle (Bromelia karatas) fruits, as well as the antibacterial effect of their pre-purified proteases - Efigenia, Montalvo-González; Miguel, Anaya-Esparza Luis; Pay, Martínez-Olivo Abraham Osiris, Abreu; Alberto, Sánchez-Burgos Jorge; Lourdes, García-Magaña María de (Emirates Journal of Food and Agriculture, 2021)
The objective was to study the behavior of the respiration rate (RR) of guamara and cocuixtle fruits during storage, the effect or the maturity stage (green maturity and consumption maturity) of these fruits on physicochemical parameters and specific proteolytic activity, as well as the antibacterial effect of the prepurified proteases of these fruits. The guamara and cocuixtle fruits presented a RR of 15 mL CO2/kg·h and 10 mL CO2/kg·h, respectively; and because the ethylene production was not detected in any of the species, it was concluded that both fruits are of the non-climacteric type. The cocuixtle fruits presented the highest specific enzymatic activity in the state of green maturity and the guamara fruits in the state of consumption maturity, with 18.99 and 53.88 U/mg of protein, respectively. Likewise, pre-purified proteases from both fruits showed antibacterial activity against E. coli and S. aureus. It is concluded that ripened guamara fruits and green cocuixtle fruits can be an important source of proteases for the food industry and they can be used against pathogens.